Criteria for Assessing a Classic Grounded Theory Study - Kara L. Vander Linden; Patrick A. Palmieri (Grounded Theory Review: An International Journal, 2021)
Introduction: Reporting criteria for research studies are essential to assess the methods and to evaluate the usefulness of the findings. The purpose of this review was to identify the essential criteria to report a classic grounded theory (classic GT) study.